A comparison of Asian airlines websites quality: using a non-parametric test. (1st January 2011) - Dominic, P.D.D.; Jati, Handaru
This research conducts test to measure the quality of Asian airlines website via web diagnostic tools online. We propose a methodology for determining and evaluating the best airlines website based on many criteria of website quality, consist of linear weightage model (LWM), analytical hierarchy process, fuzzy analytical hierarchy process (FAHP) and one new hybrid model (NHM). This NHM has been implemented using combination FAHP and LWM. The result of this study confirmed most of Asian websites are neglecting performance and quality criteria. By applying hybrid model approach has resulted in significant acceleration of implementation, raised the overall effectiveness and enabled more efficient procedure. To compare ranking methods, a combination of Friedman's test and Dunn's multiple comparison procedure is adopted.